Shallow magma convection evidenced by excess degassing and thermal radiation during the dome-forming Sabancaya eruption (2012–2020) - Coppola, Diego (2022)
We used a large set of satellite- (visible, infrared, and radar images from Planetscope, MODIS, VIIRS, Sentinel2, Landsat 8, and Sentinel 1) and ground-based data (optical images, SO2 flux, shallow seismicity) to describe and characterize the activity of the Sabancaya volcano during the unrest and eruption phases that occurred between 2012 and 2020. The unrest phase (2012–2016) was characterized by increasing gas and thermal flux, sourced by a convective magma column rising along with the remnants of a buried plug still permeable to fluid flow. Conversely, a new conduit, adjacent to the previous one, fed the eruptive phase (2016–2020) which was instead characterized by a discontinuous extrusive activity, with phases of dome growth (at rates from 0.04 to 0.75 m3 s−1) and collapse. The extrusive activity was accompanied by fluctuating thermal anomalies (0.5–25 MW), by irregular SO2 degassing (700–7000 tons day−1), and by variable explosive activity (4–100 events d−1) producing repeated vulcanian ash plumes (500–5000 m above the crater). Magma budget calculation during the eruptive phase indicates a large excess of degassing, with the volume of degassed magma (0.25–1.28 km3) much higher than the volume of erupted magma (< 0.01 km3). Similarly, the thermal energy radiated by the eruption was much higher than that sourced by the dome itself, an unbalance that, by analogy with the degassing, we define as “excess thermal radiation”. Both of these unbalances are consistent with the presence of shallow magma convection that fed the extrusive and explosive activity of the Sabancaya dome.